Intervista a Ivan Fedele - Ligabue, Marco (Musica/Tecnologia, 2010)
The interview to Ivan Fedele – which opens this number of Music / Technology as ‘provoking’ element – expresses the composer’s attitude towards technology – mainly found in computer music –, the use he made within his work, as well as the developments generally considered harbingers of more interesting perspectives for the future. Several passages stress the primacy of the compositional idea on the technological means and the need of the composer to maintain control of the situation without giving up the prerogatives of the medium; indeed, it must be ‘bent’ – if not specifically designed – to the requirements of the compositional idea.